Pengaruh Promosi dan Brand Awareness Terhadap Kemantapan Keputusan Menjadi Nasabah Bank BJB Kantor Cabang Rawamangun - Fitria, Alvina Detalindhan; Ariandi, Fajri; Fitra, Safrezi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The development of the banking industry requires every bank to improve its marketing strategies in order to attract and retain customers. One of the challenges faced by Bank BJB Rawamangun Branch is how promotion and brand awareness can influence prospective customers’ confidence in making the decision to become part of Bank BJB Rawamangun’s services. This study aims to obtain empirical evidence regarding the influence of promotion and brand awareness on the confidence of decision-making to become a customer of Bank BJB Rawamangun Branch. The research population consists of new and prospective customers, with a sample size of 100 respondents determined through purposive sampling using the Slovin formula. Data analysis was conducted using SPSS Version 25 through multiple linear regression, including validity tests, reliability tests, classical assumption tests, as well as t-tests, F-tests, and the coefficient of determination. The results show that promotion has a positive and significant effect (sig 0.02; t-count 2.277 t-table 1.98552), as does brand awareness (sig 0.01; t-count 4.328 t-table 1.98552). The simultaneous test resulted in F-count 51.937 F-table 3.09 with sig 0.000, indicating that both variables have a significant joint effect. The R² value of 0.517 indicates that promotion and brand awareness explain 51% of the variation in customer decision-making, while the remaining 49% is influenced by other factors outside the research model.